2023
DOI: 10.1101/2023.06.08.544238
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Substantial variation in species ages among vertebrate clades

Abstract: Ecological and evolutionary studies traditionally assume that species are comparable units of biodiversity. However, not only this assumption is rarely tested, but also there have been few attempts even to assess variation in most emergent, species-level traits and their corresponding underlying mechanisms. One such trait is species age, here defined as the time since the most recent common ancestor between a given species and its sister lineage. In this study, we demonstrate that different terrestrial vertebr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…For example, Sonne et al (2022) determined young and old Andean hummingbirds by assessing the sensitivity of their results to incomplete taxon sampling by generating 1000 trees with randomly missing species. Pie & Caron (2023) accounted for taxonomic incompleteness by pruning an additional 1 -5% of species and evaluated if their conclusions changed and found that they did not. Yet, the magnitude of the error associated with the direct use of the length of phylogenetic branches as estimators of species ages remains under-appreciated, as shown by the many studies implementing this approach.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, Sonne et al (2022) determined young and old Andean hummingbirds by assessing the sensitivity of their results to incomplete taxon sampling by generating 1000 trees with randomly missing species. Pie & Caron (2023) accounted for taxonomic incompleteness by pruning an additional 1 -5% of species and evaluated if their conclusions changed and found that they did not. Yet, the magnitude of the error associated with the direct use of the length of phylogenetic branches as estimators of species ages remains under-appreciated, as shown by the many studies implementing this approach.…”
Section: Discussionmentioning
confidence: 99%
“…The use of branch lengths of phylogenetic trees as an approximation of species ages is becoming central to an increasing number of studies that use them to evaluate the relationship among macro-ecological and evolutionary patterns and current extinction risks (Pie & Caron, 2023;Sonne et al, 2022;Tanentzap et al, 2020;Verde Arregoitia et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations